PENGARUH PRINSIP GOOD GOVERNANCE DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA JAKARTA GAMBIR TIGA - Silmi Kaffah; Supriyono (Jurnal Ilmu Administrasi Publik, 2026)
This study examines the effect of Good Governance Principles and Tax Knowledge on Individual Taxpayer Compliance at KPP Pratama Jakarta Gambir Tiga. The study was motivated by the declining level of taxpayer compliance despite the increasing number of active taxpayers. A quantitative approach with an associative research design was employed. The population consisted of 2,384 active individual taxpayers, with a sample of 100 respondents selected using the accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that Good Governance Principles have a positive and significant effect on Individual Taxpayer Compliance with a contribution of 16.3%, while Tax Knowledge has a positive and significant effect with a contribution of 39.6%. Simultaneously, Good Governance Principles and Tax Knowledge have a positive and significant effect on Individual Taxpayer Compliance with a contribution of 39.2%.